24.5k views
0 votes
How to find nth term for a sequence of following numbers;

1,9,36,100...? I know that this is square sequence and I use the formula a+(n-1)d+1/2×(n-1)×(n-2)c where a=the first term of first sequence d=difference between first two terms in first sequence and c=common difference between terms in the second difference. How to express c in this example if the terms in the second sequence are cube numbers? please help

User Rashanna
by
5.5k points

1 Answer

3 votes

Let
a_n denote the given sequence.
a_n has forward differences

{9 - 1, 36 - 9, 100 - 36, ...} = {8, 27, 64, ...} = {2^3, 3^3, 4^3, ...}

If we call the sequence of forward differences
b_n, then for
n\ge1,


b_n=(n+1)^3


b_n is defined in terms of
a_n for all
n\ge1 by


b_n=a_(n+1)-a_n

and so
a_n is defined recursively by


a_n=\begin{cases}a_1=1\\a_(n+1)=a_n+(n+1)^3&\text{for }n\ge1\end{cases}

We can deduce a pattern for the general
n-th term:


a_2=a_1+2^3


a_3=a_2+3^3=a_1+\displaystyle\sum_(i=1)^2(i+1)^3


a_4=a_3+4^3=a_1+\displaystyle\sum_(i=1)^3(i+1)^3

and so on, up to


a_n=a_1+\displaystyle\sum_(i=1)^(n-1)(i+1)^3

We can simplify the right hand side a bit, noticing that
a_1=1=1^3 matches
(i+1)^3 for
i=0:


a_n=\displaystyle\sum_(i=0)^(n-1)(i+1)^3

and to simplify things a bit more, we shift the index of summation:


a_n=\displaystyle\sum_(i=1)^ni^3

You should know that the right side has a nice closed form (look up "Faulhaber's formula" if you don't):


a_n=\frac{n^2(n+1)^2}4

User Jonathan Soifer
by
5.8k points